2014
DOI: 10.1352/1944-7558-119.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Everyday Executive Functioning in Young Children With Down Syndrome

Abstract: We investigated executive functioning (EF) in children with Down syndrome (DS; n = 25) and typically developing (TD) children matched for mental age (MA; n = 23) using the Behavior Rating Inventory of Executive Function-Preschool. We sought to (1) compare children with DS to a developmentally matched control group, and (2) to characterize the EF profile of children with DS. Across teacher and parent reports, significant deficits in working memory and planning were observed in the DS group. Parents, but not tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(183 citation statements)
references
References 59 publications
14
164
4
1
Order By: Relevance
“…Several studies in young individuals with DS have reported EF deficits when employing individually administered assessments, including deficits in working memory (Rowe, Lavender, & Turk, 2006; Vicari, Carlesimo, & Caltagirone, 1995) and cognitive flexibility (Lanfranchi, Jerman, Dal Pont, Alberti, & Vianello, 2010). Parent and caregiver report measures have demonstrated a consistent profile of EF strengths and weaknesses on the Behavior Rating Inventory of Executive Function – Preschool version (BRIEF–P) in children with DS, including deficits in working memory and planning, but not in inhibition or emotional control (Daunhauer et al, 2014; Gioia, Espy, & Isquith, 2003; Lee et al, 2011). A thorough consideration of this domain is also important for tracking markers of cognitive decline in DS, as there is evidence to suggest decline in EF in early to mid-adulthood may precede the onset of Alzheimer disease (Ball et al, 2006; Ball, Holland, Treppner, Watson, & Huppert, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in young individuals with DS have reported EF deficits when employing individually administered assessments, including deficits in working memory (Rowe, Lavender, & Turk, 2006; Vicari, Carlesimo, & Caltagirone, 1995) and cognitive flexibility (Lanfranchi, Jerman, Dal Pont, Alberti, & Vianello, 2010). Parent and caregiver report measures have demonstrated a consistent profile of EF strengths and weaknesses on the Behavior Rating Inventory of Executive Function – Preschool version (BRIEF–P) in children with DS, including deficits in working memory and planning, but not in inhibition or emotional control (Daunhauer et al, 2014; Gioia, Espy, & Isquith, 2003; Lee et al, 2011). A thorough consideration of this domain is also important for tracking markers of cognitive decline in DS, as there is evidence to suggest decline in EF in early to mid-adulthood may precede the onset of Alzheimer disease (Ball et al, 2006; Ball, Holland, Treppner, Watson, & Huppert, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The preschool version was administered because items were more appropriate for the nonverbal mental ages of the participants with DS. Because a number of participants fell outside of the norming sample, the raw total composite score was used in analyses, consistent with prior studies examining executive functioning in individuals with DS (Daunhauer et al, 2014; Lee et al, 2011; Liogier d’Ardhuy et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…No statistically significant difference was verified between the three groups evaluated. Literature highlights the heterogeneity in the performance pattern of children with DS 2,[10][11][12][13][14][15][16]29 . and no designation.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to consider the innumerable intrinsic and extrinsic variables that influence the cognitive and language development, which culminate in the heterogeneity of the personal functioning found in children with DS [10][11][12][13][14][15][16] . However, some authors have pointed out the neuropsychological profile of the child with DS is characterized by the lack of homogeneity in development between the cognitive and language skills with a bigger language impairment 17 .…”
Section: Introductionmentioning
confidence: 99%